Komunikasi Kerja Antar Kementrian Dilihat Dari Sudut Pertahanan Negara - Herlia, Tati (Universitas Serang Raya, 2019)
Work communication between Ministries is currently not optimal. This is due to the specific duties ofeach Ministry. But in implementing the government development program contained in Nawacita,communication between ministries must be carried out. This time the author tries to put forth writingon inter-ministerial communication seen from the point of view of national defense. Case studyactivities were analyzed through predictions of perceptions of activities in the ministry of agriculture,the ministry of transportation, the ministry of communication and information and the DPR - RI. Thetheory used is the theory of communication. The method used is qualitative analytical methods. Theresults of predictions of perceptions of analysis found several strengths in the case studies of theministry of agriculture faced with national defense and several weaknesses in the case studies of theministries of transportation and communication faced with national defense. So that the Ministry ofDefense is expected to need to participate in helping a number of conditions of weaknesses andshortcomings between these ministries as a form of communication between ministries.